Comparative Analysis of TKBM and TKSS Workers' Wage Payment Systems at the Yos Sudarso Port Cooperative, Ambon - Reza Abdulmudy; Yunita Marasabessy; Sony Ardian; Fitriah Bidari Latuconsina; Fradana Firdiantoni Afsoh; Pangeran Sidiq M. Sangadji; Rahul Lestaluhu; Hawa Aulia Ulfa Pattimahu (JURNAL ECONOMINA, 2026)
This study aims to analyze the wage payment system for Stevedoring Workers (TKBM) and Stuffing Stripping Workers (TKSS) at the Stevedoring Workers Cooperative (TKBM) of Port Yos Sudarso Class 1 Ambon, focusing on its compliance with the principles of fairness and reasonableness. This research employs a descriptive qualitative approach with data collection techniques through in-depth interviews, observation, and documentation studies. The research informants comprised 72 individuals, including the Deputy Chairman of the TKBM Cooperative, 10 group foremen, 60 regular TKBM and TKSS workers, and one operational staff member from PT Antali Jaya Mandiri Ambon. Data analysis followed the Miles and Huberman interactive model. The results indicate that the TKBM wage payment system satisfies both fairness and reasonableness principles, with actual wages ranging from Rp3,000,000 to Rp3,500,000 per month, exceeding the 2025 Maluku Provincial Minimum Wage of Rp3,141,899. Conversely, TKSS wages are only Rp1,000,000 per month, falling significantly below the minimum wage standard, thus satisfying fairness but failing reasonableness. When wages from both types of work are combined, regular workers receive total monthly earnings of Rp4,000,000 to Rp4,500,000, which satisfies both principles. This study concludes that although the wage system generally complies with the regulatory framework of Law Number 13 of 2003 and Minister of Transportation Regulation Number PM 57 of 2020, specific improvements are needed for TKSS worker remuneration to address the wage gap and ensure all port laborers receive fair and reasonable compensation.